Correla????o entre a for??a de preens??o manual e a for??a da musculatura respirat??ria em mulheres asm??ticas e n??o asm??ticas - Castro, Renata da N??brega Souza de (2009)
Asthma is a chronic inflammatory disease characterized for hiperesponsivity of airflow and imposes boundaries to patient daily activities, interfering in leisure, work and in daily life activities. The weakness of respiratory muscles hazards lung effectiveness and manovacuometry is the specific technique used to evaluate respiratory muscle strength. Handgrip strength has been used as an indicator of functional integrity and total body strength. This study aimed to make a correlation between respiratory muscle strength, hand-grip strength and asthma seriousness in ill and healthy people. This research is classified as a transversal study and the sample was composed by 80 women, from which 40 were asthmatic and 40 were healthy. The hydraulic hand dynameters, Chattanooga?? brand, was used to measure hand-grip strength and the manovacuometry, Suporte?? brand, was used to measure respiratory muscle strength. In order to make the statistical analysis, p 0,05 value was used. Results: hand-grip strength was lower in dominant hand of both groups and the asthmatic women had less respiratory muscle strength. These differences can be considered statistically significant. It was also verified that as more serious is the asthma, lower is the hand-grip strength, although with no statistical significance. The linear regression analysis showed that hand-grip strength can predict respiratory muscle strength. The results of this study indicate that the use of hand-grip strength evaluation is a trustable technique to measure the risks of these patients to present functions limitations.